Locational choice and secondary movements from the perspective of forced migrants: A comparison of the destinations Luxembourg and Germany - Birgit Glorius; Birte Nienaber (Comparative Population Studies (CPoS), 2022)
In 2015 and 2016, the enormous increase in asylum seekers travelling along the Balkan Route confronted the Member States of the European Union with an exceptional pressure on national asylum systems. Since then academic literature has revealed a reappraisal of the Common European Asylum System at regulative and policy implementation level, notably regarding the fair distribution of asylum seekers across Member States and regions. Yet we know very little about the locational choices of forced migrants or how those choices evolved and transformed during their journey. In this paper, we aim to shed light on those decision-making processes and (individual, subjective) locational choices based on the aspiration-ability model, drawing from a series of qualitative interviews with migrants held in Luxembourg and Germany in the context of the H2020 project CEASEVAL. We focus on the migrants' journeys to their actual recipient countries, highlighting mobility trajectories from the moment of first departure and on the process of decision-making regarding their choice of location. Then, we examine further mobility aspirations, which may lead to secondary mobility within or out of the country of residence. In the concluding section, we discuss the consequences of our findings for migration and asylum politics against the background of the "autonomy of migration" framework.
urn:nbn:de:bib-cpos-2022-06en2
Keywords: 300; Forced migrants; Locational choice; Secondary migration; Reception